Aplicacion de los marcadores RAPD a la identificacion varietal de citricos - Sanchez-Escribano, E.=700 1 Garcia-Garcia, J.; Garcia-Lidon, A.; Porras, I.; Cenis, J.L.
(Es, En)
ilus., 19 ref.
Keywords: CITRUS; MARCADORES GENETICOS; IDENTIFICACION; ESPAÑA; TAXONOMIA MOLECULAR; RAPD; PCR